Hybrid Particle-Field Model for Conformational Dynamics of Peptide Chains - Bore, Sigbjørn Løland; Milano, Giuseppe; Cascella, Michele (Journal of chemical theory and computation, 2018)
We propose the first model of a polypeptide chain based on a hybrid-particle field approach. The intramolecular potential is built on a two-bead coarse grain mapping for each amino acid. We employ a combined potential for the bending and the torsional degrees of freedom that ensures the stabilization of secondary structure elements in the conformational space of the polypeptide. The electrostatic dipoles associated with the peptide bonds of the main chain are reconstructed by a topological procedure. The intermolecular interactions comprising both the solute and the explicit solvent are treated by a density functional-based mean-field potential. Molecular dynamics simulations on a series of test systems show how the model here introduced is able to capture all the main features of polypeptides. In particular, homopolymers of different lengths yield a complex folding phase diagram, covering from the collapsed to swollen state. Moreover, simulations on models of a four-helix bundle and of an alpha + beta peptide evidence how the collapse of the hydrophobic core drives the appearance of both folded motifs and the stabilization of tertiary or quaternary assemblies. Finally, the polypeptide model is able to structurally respond to the environmental changes caused by the presence of a lipid bilayer.